Toxicity of Tetramethyl Lead Solutions to Mice and Rabbits. Issue 1 (January 1963) - Castellino, N.; Rossi, A.; Molé, R.
Abstract : A solution of tetramethyl lead, used as an antiknock agent in gasoline, was given by injection and inhalation to mice and by injection to rabbits. The signs of poisoning are described. Deaths might be delayed until 10 days after dosing.